Enabling JSON Document Stores in Relational Systems - Chasseur, Craig; Li, Yinan; Patel, Jignesh M. (Proceedings of the 16th International Workshop on the Web and Databases 2013, WebDB 2013, New York, NY, USA, June 23, 2013., 2013)
In recent years, “document store” NoSQL systems have exploded in popularity, largely driven by the adoption of the JSON data model in Web and mobile applications. The advantages of these NoSQL document store systems (like MongoDB and CouchDB) are tempered by a lack of traditional RDBMS features, notably a sophisticated declarative query language, rich native query processing constructs (e.g. joins), and transaction management providing ACID safety guarantees. With this paper, we hope to spark a discussion in the database community about how JSON data can be supported on top of a relational infrastructure, and how the best features of JSON document stores and relational databases can be combined. We present Argo, a proof-of-concept mapping layer for storing and querying JSON data in a relational system with an easy-to-use SQL-like query language. We also present NoBench, a micro-benchmark suite for queries over JSON data in NoSQL and SQL systems. Our results point to directions of how one can marry the best of both worlds, combining the ﬂexibility and interoperability of JSON with the rich query processing and transactional properties oﬀered by a traditional RDBMS.